Application of Rexroth Controlling for Inverted Pendulum - Rónai, László; Szabó, Tamás (International Journal of Engineering and Management Sciences, 2019)
This paper deals with the control of an inverted pendulum. Balancing techniques are used in great many controlling problems. The inverted pendulum problem is often used as a benchmark. The theoretical background is well-known and easy to treat. A commercially available Rexroth axis controller and a CKK compact module are used to control the input of the system, which is usually applied in industrial fields. A test bench has been designed and built. A PLC based program has been developed to swing up the pendulum from the rest location to inverted position and LQR controller is designed to balance the system.